Insect frass fertilizer as soil amendment for improved forage and soil health in circular systems - Amanda J. Ashworth; Helen Carla S. Amorim; Gerson L. Drescher; Philip A. Moore; Maria Guadalupe Rojas; Juan Morales-Ramos; Ann M. Donoghue (Scientific Reports)
Abstract Insect farming is expected to increase in coming years, thus generating high quantities of frass (insect excreta). Frass valorization hinges on basic agronomic research prior to industry upscaling. Here, we investigated soil physiochemical properties, SMAF (Soil Management Assessment Framework) soil health, CO2 efflux, and bermudagrass [Cynodon dactylon (L.) Pers.] yield and quality as affected by yellow mealworm (Tenebrio molitor L.) frass [3400 and 6800 kg ha−1, low (LF) and high (HF) rates], poultry litter (PL; 3400 kg ha−1), and ammonium nitrate (AN; 67 kg N ha−1). HF increased soil C, N, P, K, and Mg by 10, 12, 44, 58, and 61%, respectively, compared to AN. Even LF increased soil P, K, and Mg by 37, 31, and 32%, respectively, relative to AN. Compared to PL, HF increased soil N, K, and Mg by 12, 30, and 35%, respectively. After two years, HF increased soil C and N stocks 2- and 3-fold, respectively, relative to AN. Forage yield and quality were similar among amendments, while SMAF and CO2 were unaffected. Frass substantially improved soil fertility and maintained forage yield, underscoring its biofertilizer value and potential to increase circularity in agroecosystems under the global backdrop of reduced availability of non-renewable fertilizers.